Entrepreneurial learning from observing role models. Issue 9 (20th October 2017) - Zozimo, Ricardo; Jack, Sarah; Hamilton, Eleanor
Abstract: This study examines entrepreneurial learning through the observation of role models. Adopting an interpretive and inductive approach, and using biographical interviews and life course techniques, the article examines how sixteen entrepreneurs articulate their entrepreneurial learning from role models. The overarching research question 'How do entrepreneurs learn from observing role models?' enables illustrating who the role models are (parents, teachers, colleagues, other entrepreneurs), the relevant social contexts (home, education, workplace) and what is learned in relation to entrepreneurial learning tasks (learning about oneself, managing relationships, the business and small business management). The study contributes to developing the social perspectives of entrepreneurial learning by demonstrating the significance of learning from role models in different social contexts and at distinct entrepreneurial stages pre- and post-start-up.